2019
DOI: 10.1634/theoncologist.2019-0932
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Trial of a Modified Vaccinia Ankara Priming Vaccine Followed by a Fowlpox Virus Boosting Vaccine Modified to Express Brachyury and Costimulatory Molecules in Advanced Solid Tumors

Abstract: Lessons Learned Modified vaccinia Ankara‐Bavarian Nordic (MVA‐BN)‐Brachyury followed by fowlpox virus‐BN‐Brachyury was well tolerated upon administration to patients with advanced cancer. Sixty‐three percent of patients developed CD4+ and/or CD8+ T‐cell responses to brachyury after vaccination. BN‐Brachyury vaccine also induced T‐cell responses against CEA and MUC1, which are cascade antigens, that is, antigens not encoded in the vaccines. Background Brachyury, a transcription factor, plays an integral role … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 22 publications
(23 reference statements)
0
18
0
Order By: Relevance
“…No congenital abnormalities, complication rate in line with expected background rates. [33] in gene therapy experiments Non-productive infection Cancer vaccines: CV301 (reference [71] ) Brachyury (references [37] , [72] ) [71] , [37] , [72] in any other special populations Non-productive infection. Non-replicating in human cell lines Atopic dermatitis: references [73] , [74] Stem cell transplant: reference [75] [73] , [74] , [75] 4.4.…”
Section: Introductionmentioning
confidence: 99%
“…No congenital abnormalities, complication rate in line with expected background rates. [33] in gene therapy experiments Non-productive infection Cancer vaccines: CV301 (reference [71] ) Brachyury (references [37] , [72] ) [71] , [37] , [72] in any other special populations Non-productive infection. Non-replicating in human cell lines Atopic dermatitis: references [73] , [74] Stem cell transplant: reference [75] [73] , [74] , [75] 4.4.…”
Section: Introductionmentioning
confidence: 99%
“…Clinical data with various brachyury vaccines have consistently demonstrated generation of a brachyury-specific T cell response in breast cancer patients ( 14 , 15 ). A recently completed phase 1 study of BN-Brachyury prime-boost vaccines showed the vaccine was well tolerated and generated brachyury-specific immune responses in patients with advanced solid tumors ( 16 ).…”
Section: Rationale For Tetratherapy Combination In Advanced Breast Camentioning
confidence: 99%
“…As discussed earlier, memory T cell responses generally expand more rapidly and to a higher degree than primary T cell responses, and this aspect of active immunity has been leveraged with primeboost immunization approaches. [79][80][81][82] Interestingly, whether it is possible to achieve true memory cell differentiation (epigenetic and metabolic) when tumor remains in a patient is a subject of debate, and may influence the vaccine scheduling. Repetitive weekly vaccines may boost effector cell responses, but may limit memory cell development as compared with monthly or more widely interspersed immunizations.…”
Section: Immunocompetencementioning
confidence: 99%
“…The impact of varying the frequency, location, and amount of vaccine can be quite different, from an immunological perspective, than from traditional pharmacodynamic/pharmacokinetic considerations. As discussed earlier, memory T cell responses generally expand more rapidly and to a higher degree than primary T cell responses, and this aspect of active immunity has been leveraged with prime‐boost immunization approaches 79–82 . Interestingly, whether it is possible to achieve true memory cell differentiation (epigenetic and metabolic) when tumor remains in a patient is a subject of debate, and may influence the vaccine scheduling.…”
Section: A Role For Cancer Vaccines In the Future Immunotherapy Repermentioning
confidence: 99%